Mapping RYR1, PIT1 and PRKAG3 using a commercial porcine population as a reference - GUO Xiao-ling; YIN Zhao-zheng; XU Ning-ying; Kalm Ernst (浙江大学学报. 农业与生命科学版)
Using a commercial porcine population produced by crossing of five swine breeds including Hampshire and Pietrain as a reference, three genes—RYR1, PIT1 and PRKAG3, which were located on chromosome 6, 13 and 15, respectively, were mapped by the method of constructing a linkage map using microsatellite markers. The results showed that RYR1 was mapped between S0087 and Sw316 on Chr.6, PIT1 between Sw225 and Sw1056 on Chr.13 and PRKAG3 between Sw946 and Sw906 on Chr.15. These results are basically in accordance with those which were reported previously by other authors.